Nutritional and Health Requirements to Achieve Quality in The Localization of Baby Food Industry - Nadia, H. Munkhi (Food Technology Research Journal)
Breastfeeding is the optimal nutrition for infants. Baby food is divided into two categories: breast milk substitutes and complementary foods. Complementary foods are any foods, whether manufactured or prepared at home, suitable to supplement breast milk or infant formula when they become insufficient to meet the infant's nutritional needs. These foods, provided to children aged 6-24 months, must adhere to strict nutritional requirements in accordance with Codex Alimentarius standards and the health and safety guidelines for children's food. The ingredients must be clean, safe, appropriate, and of high quality, and the prepared texture should be suitable for feeding infants or young children, as specified on the food label. The baby food market in the Middle East, Africa, and Egypt is projected to experience significant growth in the coming years due to increasing awareness and strict food quality regulations. Localizing the food industry in Egypt can encourage reliance on domestic products and promote exports, key government objectives for enhancing food security. The urgent need to localize the baby food industry aligns with the global trend toward localizing industries for health and security reasons, especially given the growing segment of children in need of these products.